Characterization of self-cleaving RNA sequences on the genome and antigenome of human hepatitis delta virus. - Kuo, M Y (1988)
Recently we reported that in vitro RNA transcripts complementary to the genome of hepatitis delta virus (HDV) contain a unique site at which self-cleavage can occur. Subsequent studies showed that a similar self-cleavage site was present on in vitro RNA transcripts of genomic HDV RNA. The same self-cleavage reactions were also found to occur on HDV RNAs from the livers of infected chimpanzees. Using the in vitro RNA it was also possible to determine that the minimum length of contiguous sequence needed for self-cleavage of genomic RNA was 30 bases 5' and 74 bases 3' of the cleavage site. This sequence was not compatible with the "hammerhead" structure hypothesized to be important in the self-cleavage reactions of other RNAs.